2012
DOI: 10.21273/horttech.22.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Food Safety Compliance Costs and Foodborne Illness Outbreaks in the United States

Abstract: This study investigates the potential impact of food safety outbreaks on domestic shipments, imports, and prices of the produce industry. Moreover, the compliance costs associated with new food safety standards were also estimated. Three case studies were analyzed to assess these potential impacts: the muskmelon (Cucumis melo) outbreak of Mar.–Apr. 2008, the spinach (Spinacea oleracea) outbreak of Sept. 2006, and the tomato (Solanum lyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Outbreaks are not only a risk to public health, but also frequently damage consumer confidence in the safety of the fresh produce supply chain, leading to substantial economic losses to produce growers and associated industries (19).…”
mentioning
confidence: 99%
“…Outbreaks are not only a risk to public health, but also frequently damage consumer confidence in the safety of the fresh produce supply chain, leading to substantial economic losses to produce growers and associated industries (19).…”
mentioning
confidence: 99%
“…The biggest buyers influence the entire producebuying sector (Fister Gale 2006;Havinga 2006;Ribera et al 2012). Other buyers may decide, in order to remain competitive and entice customers, to adopt similar or even more stringent food safety policies.…”
Section: Recent Impacts On Growersmentioning
confidence: 99%
“…Hardesty and Kusunose (2009) found that California leafy greens growers did not receive a price premium for implementing the compliance requirements of the Leafy Greens Marketing Agreement (LGMA), but LGMA does differ from other food safety programs as it has nearly 100% grower adoption. And although Ribera, Palma, Paggi, Knutson, and Masabn (2012) found that the compliance costs incurred by growers to demonstrate food safety assurance are much lower than the costs incurred during a produce-associated outbreak (i.e. declining sales and unsaleable product), it is unlikely that the growers with GAP certification are buffered from the volatile market during an outbreak.…”
Section: Tablementioning
confidence: 99%